STUDY OF SEASON CATCHING FISHING (Rastrelliger spp) TO ‘SIBOLGA NORTH SUMATERA PROVINCE - Juanda Wisno Sinurat; Ersti Yulika Sari; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aims to know the pattern of catching fishing seasons pattern in the Sibolga waters North Sumatera. An analysis was conducted using catching production and purse seine fishing trip from the years at 2012-2016.collected by Sibolga Fishing Port. The method used is survey method, the method to be used in this research is survey method. Survey method is conducted for primary data collection and secondary data. Primary data will be obtained through direct interviews with fishermen on fishing grounds, operation times, and fishing effortsThe result showed that The result showed that the change of catch in a certain month because of the availability of fish and the succeed of fishing operation which resulted in the CPUE to fluctuate a good time to do bloated fishing in January, July, August, and November with peak season in November. While the lowest season index is February.. Keywords: Fishing seasons,catching, the average percentage methods,and CPUE